University Museums as Library Partners in Transformation of Inclusive and Interdisciplinary Institution - Pungki Purnomo; Azwar, Muhammad; Ida Farida; Amir Fadhilah; Lili Sudria Wenny (Program Studi Ilmu Perpustakaan UIN Alauddin, 2026)
Background: In the landscape of Indonesian Islamic Higher Education, the museums at UIN Ar-Raniry Banda Aceh and UIN Maulana Malik Ibrahim Malang serve as pioneering institutional models. These repositories function as